PENGARUH CAPITAL ADEQUACY RATIO SERTA NON PERFOMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA - ., Ari Sagita Pt; ., Drs. Wayan Cipta, M.M.; ., Ni Nyoman Yulianthini, S.E., M.M. (Jurnal Manajemen Indonesia, 2019)
Penelitian ini bertujuan untuk menguji pengaruh capital adequacy ratio (CAR), non performing loan (NPL), dan loan to deposit ratio (LDR) terhadap return on asset (ROA) secara simultan maupun secara parsial. Subyek penelitian ini adalah Bank Umum Swasta Nasional Devisa yang terdaftar di Bursa Efek Indonesia dan Obyek dalam penelitian ini adalah capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR) dan return on asset (ROA). Data dikumpulkan dengan pencatatan dokumen, dan dianalisis dengan analisis regresi linier berganda. Jumlah populasi penelitian ini adalah 35 bank dan jumlah sampel 19 bank dengan melewati tahap purposive sample. Hasil penelitian menunjukkan bahwa (1) ratio capital adequacy ratio (CAR), non performing loan (NPL), dan loan to deposit ratio (LDR) berpengaruh terhadap return on asset (ROA), (2) capital adequacy ratio (CAR) berpengaruh positif dan signifikan terhadap return on asset (ROA), (3) non performing loan (NPL) berpengaruh negatif dan signifikan terhadap return on asset (ROA), (4) loan to deposit ratio (LDR) berpengaruh positif dan tidak signifikan terhadap return on asset (ROA). Kata Kunci : capital adequacy ratio, loan to deposit ratio, non performing loan, return on asset This study was to determine the influence of capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR) to return on asset (ROA) for simultaneosly or partially. The subjects of this study are National Private Foreign Exchange Bank that listing at Indonesian Stock Exchange, and the Objects in this study are capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR) and return on asset (ROA). Data is collected by recording documents, and analyzed by multiple linear regression analysis. The population of this study is 35 banks and the number of samples is 19 banks by passing the purposive sample stage. The results showed that (1) capital adequacy ratio (CAR), non performing loan (NPL), dan loan to deposit ratio (LDR) had an effect on return on asset (ROA), (2) capital adequacy ratio (CAR) had a positive and significant effect on return on asset (ROA), (3) non performing loan (NPL), had a negative and significant effect on return on asset (ROA), (4) loan to deposit ratio (LDR) had a positive and not significant effect on return on asset (ROA). keyword : adequacy ratio, loan to deposit ratio, non performing loan, return on asset